Contribution of factor structure change to China's economic growth: evidence from the time-varying elastic production function model. Issue 1 (1st January 2020) - Zhang, Shangfeng; Liu, Yaoxin; Huang, Duen-Huang
Abstract: The time-varying factor share runs through the entire process of the Chinese economic miracle, unlike the 'Kaldor Facts' in developed countries. Following the new structural economics theory, we construct a time-varying elastic production function model that characterises the structural changes of China's economic element, and decompose the driving force of economic growth to measure the contribution of factor structure. We found that, from 1978–2017, the average contribution of capital, labour, technological progress, and factor structure change to the GDP was 67.01%, 10.38%, 23.08%, and −0.47%, respectively. The measurement results can aptly portray the impact of policy changes in China's unique gradual reform process, such as the economic market reforms in 1992, the global financial crisis in 2008, and the policy changes of the new economic normal in 2014. Meanwhile, the results reveal that improving factor allocation can accelerate the total factor productivity and promote high-quality development of China's economy.